Application of high-quality nursing for COVID-19 patients in makeshift hospitals (优质护理在方舱医院内新型冠状病毒肺炎患者中的应用) - YAN Haichun (闫海春); MI Yuehua (米跃华); ZHAO Chunhua (赵春华); SUN Hongyan (孙红艳); YOU Xin (尤欣); LI Liyuan (李莉媛); ZHANG Xiaoyun (张潇允); MA Lixin (马立新); ZHANG Kungang (张坤岗); JIA Qiong (贾琼); XIAO Jiale (肖嘉乐); HAN Miaomiao (韩苗苗); et al. (中西医结合护理)
Objective To investigate the effect of high-quality nursing for COVID-19 patients in makeshift hospitals. Methods A medical team of doctors and nurses was established to participate in the nursing of 528 COVID-19 patients in makeshift hospitals. A high-quality nursing program including environment evaluation, psychological care, sleep quality improvement, symptomatic care, safety management and diet care. Results There was no death or nosocomial infection case reported. No serious adverse event was reported throughout the study. Conclusion High-quality nursing plays an important role in relief of negative emotion, prevention of cross-infection and promotion of rehabilitation among COVID-19 patients in makeshift hospitals. (目的 探讨优质护理在方舱医院内新型冠状病毒肺炎患者中的应用效果。方法 医疗队援沪期间共参与方舱医院内528例新型冠状病毒肺炎确诊患者的护理工作, 护理内容包括环境评估、心理护理、睡眠护理、症状护理、安全及饮食护理等方面实施优质护理。结果 援沪期间, 舱内患者无死亡, 无院内感染和不良事件发生, 均痊愈出舱。结论 优质护理体现了以人文本的护理理念, 在缓解患者负性情绪、预防交叉感染、促进患者康复方面有着重要作用。)